BORDIR KERANCANG DI KOTA PADANG PANJANG - Rasyid, Ranny; Nazar, Ernawati ,; Nelmira, Weni (Journal of Home Economics and Tourism, 2017)
Padang Panjang has Kerancang embroidery very beautiful and charming. This study aimed to describe Kerancang embroidery designs, embroidery Kerancang forms, tools and materials used in the manufacture of embroidery Kerancang and manufacturing technique of embroidery Kerancang in Padang Panjang. This research method is descriptive qualitative. Data was collected using interview, observation and documentation. Data analysis techniques are data reduction, data presentation, and conclusions. The validity of the data with the extension of 3observation, improved observations and triangulation. The study states that the embroidery Kerancang in Padang Panjang has a decorative shape naturalist, geometric shapes, and decorative shapes. Kerancang form of embroidery used were 16 shapes. Tools and materials used in making embroidery Kerancang pencils, paper rolls, erasers, carbon, fabric, sewing machine manual that has been tuned to make embroidery Kerancang, needle machine brand singer number 11 and number 9, sikoci, ram, embroidery scissors and yarn branded embroidery double penguin. The technique of making embroidery Kerancang a sewing machine sewn manual or dikerancang directly. Stage manufacturing embroidered Kerancang, starting from trace motif, small suji delicate motif and shearing, start mengkerancang, then the process of finishing with smoothed Kerancang.Keywords: Embroidery Kerancang, Embroidery Motif, Kerancang Form, Tools And Materials Used In The Manufacture Of Embroidery Kerancang, Technique Embroidery.